The body speaks before it even talks: deliberation, populism and bodily representation - Casullo, María Esperanza (2020)
Fil: Casullo, María Esperanza. Universidad Nacional de Río Negro. Laboratorio de Estudios e Investigación en Sistema Penal y Derechos Humanos. Río Negro, Argentina.